Docophorulus fedorenkoae sp. n. (Mallophaga) — пухоед дроздовидной камышевки - Мей, Э. (Вестник зоологии, 1983)
The paper presents an illustrated description of Docophorulus fedorenkoae sp. n. from great reed warbler (Turkmen SSR). It is distinct by colouration, larger body size, dorsal spines number on the last abdominal segment and by a special structure of the basal plate immediately before parameres. The new species is included in the modularis species group.